2017
DOI: 10.1038/celldisc.2017.40
|View full text |Cite
|
Sign up to set email alerts
|

Binding to RNA regulates Set1 function

Abstract: The Set1 family of histone H3 lysine 4 (H3K4) methyltransferases is highly conserved from yeast to human. Here we show that the Set1 complex (Set1C) directly binds RNA in vitro through the regions that comprise the double RNA recognition motifs (dRRM) and N-SET domain within Set1 and its subunit Spp1. To investigate the functional relevance of RNA binding, we performed UV RNA crosslinking (CRAC) for Set1 and RNA polymerase II in parallel with ChIP-seq experiments. Set1 binds nascent transcripts through its dRR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 57 publications
2
36
0
Order By: Relevance
“…Previous studies have demonstrated that the methyltransferase activity of SETD1A toward H3K4 is mediated by its C-terminal N-SET (COMPASS component N-Su(var)3-9, Enhancer-of-zeste, Trithorax domain) and SET catalytic domains, whereas interactions with WDR82, RNA, and RNA polymerase II (Pol II) occur via the N-terminal RRM domain ( Lee and Skalnik, 2008 , Luciano et al., 2017 , Schlichter and Cairns, 2005 ). To examine which of these domains is required for fork protection by SETD1A, we established U-2-OS cell lines in which endogenous SETD1A could be depleted with small interfering RNA (siRNA), and either full-length (FL) FLAG-tagged SETD1A or variants lacking the RRM (ΔRRM) or catalytic SET (ΔSET) domains could be inducibly expressed ( Figures S3 A and S3B).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that the methyltransferase activity of SETD1A toward H3K4 is mediated by its C-terminal N-SET (COMPASS component N-Su(var)3-9, Enhancer-of-zeste, Trithorax domain) and SET catalytic domains, whereas interactions with WDR82, RNA, and RNA polymerase II (Pol II) occur via the N-terminal RRM domain ( Lee and Skalnik, 2008 , Luciano et al., 2017 , Schlichter and Cairns, 2005 ). To examine which of these domains is required for fork protection by SETD1A, we established U-2-OS cell lines in which endogenous SETD1A could be depleted with small interfering RNA (siRNA), and either full-length (FL) FLAG-tagged SETD1A or variants lacking the RRM (ΔRRM) or catalytic SET (ΔSET) domains could be inducibly expressed ( Figures S3 A and S3B).…”
Section: Resultsmentioning
confidence: 99%
“…Activation of Rad6/Bre1 and COMPASS recruitment also require interactions with the Ser-5 phosphorylated CTD of RNA polymerase II, providing a tight transcriptional connection ( Krogan et al, 2003 ; Ng et al, 2003 ; Xiao et al, 2005 ). COMPASS recruitment then occurs through interactions of Swd2 with active H2B-associated Rad6/Bre1, and of Set1/Spp1 with nascent mRNA ( Battaglia et al, 2017 ; Luciano et al, 2017 ; Sayou et al, 2017 ; Thornton et al, 2014 ). In mammals, additional CxxC domains in Cfp1 (the orthologue of yeast Spp1) and some SET-domain proteins further specify and diversify COMPASS activity, allowing DNA methylation-dependent activity and selective recruitment of COMPASS to promoter and enhancer sequences ( Brown et al, 2017 ; Clouaire et al, 2012 ; Hu et al, 2017 ; Thomson et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Activation of Rad6/Bre1 and COMPASS recruitment also require interactions with the Ser-5 phosphorylated CTD of RNA polymerase II, providing a tight transcriptional connection (Krogan et al, 2003;Ng et al, 2003;Xiao et al, 2005). COMPASS recruitment occurs through interactions of Swd2 with active H2B-associated Rad6/Bre1, and of Set1/Spp1 with nascent mRNA (Battaglia et al, 2017;Luciano et al, 2017;Sayou et al, 2017;Thornton et al, 2014). In mammals, additional CxxC domains in Cfp1 (the orthologue of yeast Spp1) and some SETdomain proteins further specify and diversify COMPASS activity, allowing DNA methylationdependent activity and selective recruitment of COMPASS to promoter and enhancer sequences (Brown et al, 2017;Clouaire et al, 2012;Hu et al, 2017;Thomson et al, 2010).…”
Section: Introductionmentioning
confidence: 99%